Mandibular and temporomandibular morphologic characteristics of patients with suspected unilateral condylar hyperplasia: a CT study - López,Diego Fernando (2020)
ABSTRACT Introduction: Facial asymmetry associated with unilateral condylar hyperplasia (UCH) is a complicated clinical condition. Objective: The objective of this study was to describe morphological characteristics of the mandible and the temporomandibular joint in patients with facial asymmetry, using computed tomography and 3D reconstruction. Methods: A retrospective observational study was performed with patients displaying facial asymmetry evaluated by single photon emission computed tomography (SPECT)/CT analysis, for suspected UCH, between 2015 and 2018. The following variables were compared between the affected side (producing the asymmetry) and the contralateral side (side to where the jaw is deflected): condylar length, condylar medial and lateral pole length, mandibular ramus length, intra-articular spaces, articular eminence height and position of the posterior wall of the glenoid fossa. Results: Forty-three patients (21 women, mean age: 20.7 ± 7.25 years) with facial asymmetry were included, 19 patients presented right side deviation and 24 patients had left side deviation. Condylar length, lateral pole length, the sum of maximum values and articular eminence height were greater in the affected side (p< 0.05). A positive correlation was found between the position of the posterior wall of the glenoid fossa and the articular eminence height in the affected side (r = 0.442). Conclusions: In patients with suspected UCH, evaluated through CT, craniofacial measurements showed significantly larger condylar length and the condylar sum of maximum values in the affected side. A positive correlation was found between the increased dimensions of the articular eminence and the more posterior position of the glenoid fossa in the affected side.